Travel, sexuality and female Indonesian domestic migrant workers in Hong Kong. Issue 5 (3rd September 2019) - Allmark, Panizza; Wahyudi, Irfan
ABSTRACT: In Hong Kong Indonesian migrant domestic workers (IMDWs) face strict working conditions and are vulnerable to human rights abuses and exploitation. Nevertheless, travelling abroad has provided the opportunity for somewhat greater freedom, agency and the opportunity to express a more fluid sexual identity, than in their home country where there has been a push to a more conservative moral heterosexual agenda. This article examines a group of lesbian Indonesian migrant domestic workers, named PL. Through fashion and behaviour they challenge conservative and normative comportment of Indonesian women. In particular with reference to the growing concerns for sexual freedom in Indonesia, it is important to consider how same-sex relationships and gender-fluid activity is enacted outside of the national context. This research explores how IMDWs articulate their romantic and sexual needs in a foreign land which has created somewhat new identities, love relationships and life balance from what they may experience in their homeland.